2022
DOI: 10.17016/ifdp.2022.1339
|View full text |Cite
|
Sign up to set email alerts
|

Reusing Natural Experiments

Abstract: After a natural experiment is first used, other researchers often reuse the setting, examining different outcome variables. We use simulations based on real data to illustrate the multiple hypothesis testing problem that arises when researchers reuse natural experiments. We then provide guidance for future inference based on popular empirical settings including difference-in-differences regressions, instrumental variables regressions, and regression discontinuity designs. When we apply our guidance to two exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Our findings from a fitted crash, obtained from the 1st stage regression, support our baseline specification results and pass the conventional t-statistics. Heath et al (2023) discuss the potential concerns arising from the same instrument being used for multiple objectives. We follow Heath et al (2023) and use their suggested heuristic that our results should pass the t-statistics of 3.00.…”
Section: Mutual Fund Flow Hypothetical Sale As An Exogenous Variablementioning
confidence: 99%
See 3 more Smart Citations
“…Our findings from a fitted crash, obtained from the 1st stage regression, support our baseline specification results and pass the conventional t-statistics. Heath et al (2023) discuss the potential concerns arising from the same instrument being used for multiple objectives. We follow Heath et al (2023) and use their suggested heuristic that our results should pass the t-statistics of 3.00.…”
Section: Mutual Fund Flow Hypothetical Sale As An Exogenous Variablementioning
confidence: 99%
“…Heath et al (2023) discuss the potential concerns arising from the same instrument being used for multiple objectives. We follow Heath et al (2023) and use their suggested heuristic that our results should pass the t-statistics of 3.00. Heath et al (2023) use the correction method from Wolf (2005, 2016) and suggest adjusting t-statistics to address the multiple testing concern.…”
Section: Mutual Fund Flow Hypothetical Sale As An Exogenous Variablementioning
confidence: 99%
See 2 more Smart Citations
“…One concern is that broker house mergers and closures have been used in several existing studies raising Heath et al (2023). provide adjusted critical values depending on how many previous outcomes have been examined using the same setting.…”
mentioning
confidence: 99%